Intervención fisioterapéutica en paciente de sexo femenino de 33 años, con dolor lumbar crónico. - Sánchez Jaime, Reyna Elizabeth (2025)
Chronic low back pain is one of the leading causes of disability in adults and significantly impacts the quality of life of those affected. This condition may be associated with factors such as muscle weakness, postural problems, and intervertebral disc degeneration, limiting functionality and causing continuous discomfort. In this context, physical therapy plays a fundamental role in the treatment of chronic low back pain, helping to reduce pain, improve mobility, and strengthen the lumbar muscles. This study presents the clinical case of a 33-year-old female patient with chronic low back pain who sought physical therapy treatment at the Hospital General Martin Icaza due to persistent pain over the past six months, which has limited her ability to perform daily activities. Through a comprehensive physical evaluation, functional alterations were identified, such as reduced lumbar mobility and pain during specific movements. The physiotherapeutic intervention included various therapeutic strategies, such as manual therapy, therapeutic exercises (Williams, proprioception, muscle strengthening), physical agents like electrotherapy and infrared, and postural education to prevent relapses. Weekly follow-ups were conducted to adjust the treatment and measure the patient's progress. The results showed a decrease in pain, improved lumbar mobility, and increased muscle strength, allowing the patient to regain part of her functionality. This case highlights the importance of an integrated and personalized physiotherapeutic intervention in the treatment of chronic low back pain, promoting strategies that enable patients to improve their quality of life and prevent future complications.